2016
DOI: 10.1002/jocb.157
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Wording and Placement of Task Instructions on Problem‐Solving Creativity

Abstract: Prior research has used many variants of "be creative" or brainstorm instructions to enhance creativity in a variety of tasks. However, differences in instruction wording may lead to differences in instruction interpretation, and varying the placement of instructions before or after a written problem description may lead to differences in problem interpretation. This study investigated the effect of varying the wording and placement of creativity instructions on idea novelty, workability, and effectiveness. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…This methodological choice (see also Howard-Jones et al, 2005; Niu & Sternberg, 2001; O’Hara & Sternberg, 2001) leaves the decision about what makes a response creative incumbent on the participant, who is free to respond with a novel but potentially inappropriate response. Few studies have directly manipulated the amount of guidance given with the explicit cue in how to be creative (Amabile, 1979; Di Mascio et al, 2016; Niu & Liu, 2009). One reason for this is that the use of specific guidance raises several methodological concerns.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This methodological choice (see also Howard-Jones et al, 2005; Niu & Sternberg, 2001; O’Hara & Sternberg, 2001) leaves the decision about what makes a response creative incumbent on the participant, who is free to respond with a novel but potentially inappropriate response. Few studies have directly manipulated the amount of guidance given with the explicit cue in how to be creative (Amabile, 1979; Di Mascio et al, 2016; Niu & Liu, 2009). One reason for this is that the use of specific guidance raises several methodological concerns.…”
Section: Methodsmentioning
confidence: 99%
“…To perform such a test, the present study utilized a set of cue conditions that, to our knowledge, has not been utilized before in creativity cue research (for the closest approximation, see Runco et al, 2005). Many explicit cue studies have compared creative performance across a creative and uncreative condition for a variety of tasks, including divergent thinking (Datta, 1963; Harrington, 1975; Di Mascio, Kalyuga, & Sweller, 2016; Nusbaum, Silvia, & Beaty, 2014; Runco & Okuda, 1991), collage making (Amabile, 1979; Niu & Sternberg, 2001), essay writing (O’Hara & Sternberg, 2001), story writing (Howard-Jones, Blakemore, Samuel, Summers, & Claxton, 2005), and drawing and poem writing (Chen et al, 2005). However, the present study added a third condition, to more directly ascertain the relationships between subjectively rated creativity, novelty, and appropriateness in the context of semantic distance as an assessment of creativity.…”
mentioning
confidence: 99%
“…Christensen and his colleagues (Christensen et al, 1957) concluded that more explicit instructions for participants to “be clever” results in more clever responses. Finally, a deep overview of the effects of wording and placement of instructions was published by Di Mascio et al (2018), who found again that more explicit instructions produced more novelty in responses and that it was not just a matter of repeating the same standard instructions. Recently, two different meta-analyses (Acar et al, 2020; Said-Metwaly et al, 2020) synthesized that empirical evidence and found that explicit instructions such as “be creative” and “generate good ideas” improve the DT outcomes over standard instructions to generate many responses.…”
Section: Discriminant Evidence Of Construct Validitymentioning
confidence: 99%
“…The same is true for studies that did not adopt the psychometric approach to object creativity. The feasibility criterion is only used when the outputs comes under the heading ideas (Diehl & Stroebe, 1991;Di Mascio, Kalyuga & Sweller, 2018;Lonergan, Scott & Mumford, 2004;Potter & Balthazard, 2004). Nevertheless, this dimension seems fundamental when talking about creativity.…”
Section: Establishing the Criteria For Creativitymentioning
confidence: 99%